COVID‐19 vaccination in patients with heart failure: a position paper of the Heart Failure Association of the European Society of Cardiology. (5th December 2021) - Rosano, Giuseppe; Jankowska, Ewa A.; Ray, Robin; Metra, Marco; Abdelhamid, Magdy; Adamopoulos, Stamatis; Anker, Stefan D.; Bayes‐Genis, Antoni; Belenkov, Yury; Gal, Tuvia B.; Böhm, Michael; Chioncel, Ovidiu; et al.
Abstract: Patients with heart failure (HF) who contract SARS‐CoV‐2 infection are at a higher risk of cardiovascular and non‐cardiovascular morbidity and mortality. Regardless of therapeutic attempts in COVID‐19, vaccination remains the most promising global approach at present for controlling this disease. There are several concerns and misconceptions regarding the clinical indications, optimal mode of delivery, safety and efficacy of COVID‐19 vaccines for patients with HF. This document provides guidance to all healthcare professionals regarding the implementation of a COVID‐19 vaccination scheme in patients with HF. COVID‐19 vaccination is indicated in all patients with HF, including those who are immunocompromised (e.g. after heart transplantation receiving immunosuppressive therapy) and with frailty syndrome. It is preferable to vaccinate against COVID‐19 patients with HF in an optimal clinical state, which would include clinical stability, adequate hydration and nutrition, optimized treatment of HF and other comorbidities (including iron deficiency), but corrective measures should not be allowed to delay vaccination. Patients with HF who have been vaccinated against COVID‐19 need to continue precautionary measures, including the use of facemasks, hand hygiene and social distancing. Knowledge on strategies preventing SARS‐CoV‐2 infection (including the COVID‐19 vaccination) should be included in the comprehensive educational programmes delivered to patients with HF.